How to Remain Collegial When Pressure for Change is High? - Audrey Harroche; Christine Musselin (Emerald Publishing Limited, 2023)
The French higher education system has experienced reforms since the 2000s that gradually emphasized the executive power of universities and the centralization of decision-making. This culminated with the excellence initiatives (Idex) that concentrated 7.7 billion euros on only nine institutions to create “world-class” universities and made their leaders responsible for the local allocation of this substantial endowment. The universities' executives had four years to complete changes in governance in order to see their institution permanently awarded the title and the funding of Idex. The hiring process is one of the elements that this policy impacted the most within these universities, enabling leaders to create new kinds of positions and control the hiring process. However, by looking at the hiring practices within three different Idex, we will show that collegiality did not disappear but rather it evolved: in the three cases, the closest colleagues have been marginalized but decision-making remained collective and in the hands of academics chosen by the university executives. Variations in the intensity of this evolution could be observed according to two dimensions. First, the scientific reputation of the university: the higher it is, the less collegiality is transformed. Second, the level of external pressures: the less collegial universities have relaxed their hiring practices after the evaluation that permanently granted them the label of Idex.
10.1108/S0733-558X20230000087002; 10.1108/S0733-558X20230000087002; Revitalizing Collegiality: Restoring Faculty Authority in Universities; EBP099697181